Ovarian reserve of women with and without BRCA pathogenic variants: A systematic review and meta-analysis. (December 2021) - Gasparri, Maria Luisa; Di Micco, Rosa; Zuber, Veronica; Taghavi, Katayoun; Bianchini, Giampaolo; Bellaminutti, Serena; Meani, Francesco; Graffeo, Rossella; Candiani, Massimo; Mueller, Michael D.; Papadia, Andrea; Gentilini, Oreste D.
Abstract: Introduction: Preliminary clinical evidence suggests a detrimental effect of pathogenic variants of BRCA1 and 2 genes on fertility outcome. This meta-analysis evaluates whether women carrying BRCA mutations (BRCAm) have decreased ovarian reserve, in terms of Anti-Muellerian Hormone (AMH), compared to women without BRCAm (wild-type). Material and methods: Systematic searches of PubMed, Medline, Scopus, Embase, Science Direct and the Cochrane Library from inception until July 2020 were conducted. All studies comparing AMH level in fertile age women, with and without BRCA pathogenic variants were considered. Sub-analyses were performed according to age, presence of breast cancer, and type of mutation. Results: Among 64 studies, 10 series were included. For the entire cohort, a trend of reduced AMH level were found between BRCAm carriers and women without pathogenic variants. BRCAm carriers aged 41-years or younger had lower AMH levels compared to 41-years or younger wild type women (OR: 0.73 [95%CI-1.12;-0.35]; p = 0.0002). This finding was confirmed for BRCA1m carriers (OR: 1 [95%CI-1.96;-0.05]; p = 0.004) whereas no difference was observed between BRCA2m carriers and wild type women. The same analysis on breast cancer patients with and without BRCAm achieved the same results. Conclusion: Young BRCA1m carriers seem to have lower AMH level compared with wild type women and therefore a potential decreased ovarian reserve. Graphical abstract: Image 1 Highlights: BRCAm carriers have similar AMH levels to wild-type women. In women under 42 years old, AMH level is statistically lower in BRCA1m. Fertility preservation counselling should be offered once BRCA pathogenic variant is diagnosed.